2022
DOI: 10.3390/polym14061196
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Nanoparticles-in-Film Technology to Achieve Extended In Vivo Exposure of MK-2048 for HIV Prevention

Abstract: MK-2048 is a second-generation integrase inhibitor active against HIV, which has been applied vaginally using ring formulations. In this work, a nanoparticle-in-film technology was developed as a discrete pre-exposure prophylactic product option against HIV for an extended duration of use. A film platform loaded with poly (lactic-co-glycolic acid) nanoparticles (PNP) encapsulating MK-2048 was engineered. MK-2048 PNPs were loaded into films that were manufactured via the solvent casting method. Physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…An HIV integrase strand transfer inhibitor, MK-2048, used for HIV prevention, was incorporated into poly(lactic-co-glycolic acid) (PLGA) nanoparticles, and the nanoparticles were delivered in a PVA—PEG (polyethylene glycol) film to female macaques. This new delivery system introduced more drug to the vaginal mucosa, and PK studies indicated sustained release for up to 3 weeks in vaginal secretions ( 87 ). This approach could potentially be used to extend the release of MPT mAbs at mucosal surfaces.…”
Section: Optimizing Mab Deliverymentioning
confidence: 99%
“…An HIV integrase strand transfer inhibitor, MK-2048, used for HIV prevention, was incorporated into poly(lactic-co-glycolic acid) (PLGA) nanoparticles, and the nanoparticles were delivered in a PVA—PEG (polyethylene glycol) film to female macaques. This new delivery system introduced more drug to the vaginal mucosa, and PK studies indicated sustained release for up to 3 weeks in vaginal secretions ( 87 ). This approach could potentially be used to extend the release of MPT mAbs at mucosal surfaces.…”
Section: Optimizing Mab Deliverymentioning
confidence: 99%
“…This compound applied as a vaginal ring has the same administration route as DPV and is presently being developed as a nanoparticle film to sustain delivery (Figure 13). 103 The search for the novel INSTIs continues where a novel scaffold, compound 44, a 4-phenylpiperidine derivative amenable to chemical modification, was identified using the High-Throughput Screening.…”
Section: Diarylpyrimidine Derivativesmentioning
confidence: 99%
“…This compound applied as a vaginal ring has the same administration route as DPV and is presently being developed as a nanoparticle film to sustain delivery (Figure 13). 103 …”
Section: Current Hiv‐1 Anti‐retrovirals and The Mechanisms Of Actionmentioning
confidence: 99%
“…In the search carried out in PubMed referring to the last 5 years of publications, several articles were found about films for vaginal administration. The most cited applications were prevention of HIV transmission [124][125][126][127][128], candidiasis [129][130][131], vaginal microbial infections [132][133][134], cervical cancer [135], and genital herpes [136]. However, these studies only dealt with drugs for local action or did not indicate the site of action and therefore were not considered in the present review.…”
Section: Current Applications Of Vaginal Filmsmentioning
confidence: 99%